Pengaruh Media Kartu Bergambar Terhadap Kemampuan Membaca Pemahaman Siswa Kelas III SDS Muhammadiyah 5 Kota Tangerang - Zuanita Hershifani Uthantry; Een Unaenah, Candra Puspita Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the differences in reading comprehension skills using picture card media among third-grade students of SDS Muhammadiyah 5 Kota Tangerang. The research employed a quantitative approach with a quasi-experimental method, specifically the nonequivalent control group design. The population consisted of all third-grade students at SDS Muhammadiyah 5 Kota Tangerang, totaling 55 students. The research sample comprised two classes: the control class and the experimental class. Data collection techniques included tests, interviews, documentation, and observation. The pre-test and post-test items administered demonstrated strong reliability, with a Cronbach’s Alpha value greater than 0.388. In the t-test hypothesis testing, the post-test data for the control and experimental classes showed that the calculated t-value (t_calculated) was greater than the t-table value (5.226 > 1.673). Based on these results, the alternative hypothesis (H₁) was accepted, and the null hypothesis (H₀) was rejected. Thus, it can be concluded that there is a significant difference in reading comprehension skills when using picture card media among third-grade students of SDS Muhammadiyah 5 Kota Tangerang.